Mission as globalization : Methodists in Southeast Asia at the turn of the twentieth century - Scott, David W (David William), 1980- (Lexington Books, 2016)
This book examines the history of Methodist mission work in Southeast Asia at the turn of the twentieth century by using metaphors taken from the language of globalization to help understand the transnational social, economic, political, and religious connections developed by the mission.